PERAN SIKAP DALAM MEMEDIASI PENGARUH KESADARAN LINGKUNGAN TERHADAP NIAT BELI PRODUK HIJAU L’OCCITANE DI DENPASAR - Dewi, N. K. Mika Jan Purnama; Mandala, Kastawan (E-Jurnal Manajemen; Vol 7 No 9 (2018)DO - 10.24843/EJMUNUD.2018.v07.i09.p15, 2018)
Worsening environment makes consumers more demanding of green products, causing many companies to develop their products into green products such as on beauty products. This study purpose to explain the role of attitude in mediating the influence of environmental consciousness on the intention to purchase green beauty products of L'Occitane brand in Denpasar City. Denpasar City was this research conducted involving 90 respondents through purposive sampling method. Questionnaire where the data were collected from. Path analysis and Sobel test are used for data analysis technique. The results found that environmental consciousness has a positive and significant effect on attitudes. Environmental consciousness has a positive significance effect on purchasing intention. Attitude have a positive significance effect on purchasing intentions. The role of attitude is able to mediate the effect of environmental consciousness on the intention to purchase green beauty product of L'Occitane brand in Denpasar City. L'Occitane management must remain consistent in selling green beauty products to make it one of their advantages over other beauty products. Keywords: environmental consciousness, attitude, purchase intention